Tinjauan Atas Penggunaan Dana Desa Untuk Layanan Sarana Dan Prasarana Masyarakat Pada Desa Sukaraja Kecamatan Sukaraja - Fitriani, Fariha; Nurjanah, Yayuk; Herawati, Heti (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Implementation of Fund Budget for Village Development _______385 Submitted FEBRUARY 2024 Accepted OCTOBER 2024 JABKES Jurnal Aplikasi Bisnis Kesatuan Vol. 4 No. 3, 2024 page. 385-396 IBI Kesatuan ISSN 2807 – 6036 DOI: 10.37641/jabkes.v4i3.1938 This review aims to evaluate the optimization of village fund budget utilization for the development and services of community facilities and infrastructure, as well as to assess the reporting on the use of village funds for these purposes in Sukaraja Village, Sukaraja District. This study uses a descriptive quantitative research method to explain and describe how the Village Fund Budget is managed and reported for the development and service of community facilities and infrastructure in Sukaraja Village, Sukaraja District. Data was collected through interviews and documents, specifically the Village Fund Budget Realization Reports for the years 2021 and 2022. The findings indicate that the management and reporting of the Village Fund Budget for the development and services of community facilities and infrastructure in Sukaraja Village, Sukaraja District, have been optimally executed, and the musrembang (development planning meetings) process regarding the implementation of fund usage was effectively conducted. However, the utilization of Village Funds in Sukaraja Village should be further improved by enhancing community facilities. Keywords : Village Fund Budget, Facilities and Infrastructure, Village Governance.